Structural, morphological and optical properties of (ZnO)ₓ (ZrO2)ַ₁˗ₓnanocomposites prepared by thermal treatment method - Midala, Hamidu Ishaku (2020)
The purpose of this study was to investigate the constituents of nanomaterial that was made from zinc nitrate, zirconia nitrate and polyvinyl pyrrolidone, which is assumed as classification of novel materials. The unique product obtained through the thermal treatment process containing the zinc oxide and zirconia oxide nanocomposites as well as organic polymer. This product possesses better characteristics as compared to their nanosizes. So, the binary oxide of the nanocomposite (Zinc oxide (ZnO)) x (Zirconia oxide (ZrO2)) 1-x at constant concentration of 4g polyvinylpyrrolidone (PVP) was calcined at various temperature that was produced with thermal treatment process. Zinc and Zirconium nitrates as well as PVP (capping agent) was used to produce nanocomposite materials (ZnO) x (ZrO2)1-x s for x = 0.2, 0.5, and 0.8 molarity. To ensure the best yield, the characterization has been performed. Thermal analysis (TGA), gave the optimization of the thermal treatment technique and show the appropriate temperature to carry out the calcination process. The crystallinity of the sample was measured by using X – ray diffraction (XRD). Fourier transform infra-red (FTIR) spectroscopy analysis proved that ZnO and ZrO2 were the original compounds for the prepared nanocomposite (ZnO) X (ZrO2) 1-X. However, the morphological characterization was determined via scanning electron microscopy (SEM) and transmission electron microscopy (TEM) and were supported by XRD results. It showed the increment of the average sample sizes from 21 – 40 nm due to the increment of calcination temperature. Ultraviolet visible spectroscopy (UV-Vis) determine the gap of optical path and decreased the values for both nanocomposite ZnO and ZrO2. Photoluminescence (PL) displayed the increment of intensity when the particle size was increased. The study also showed the application of optical in the binary particle application with the wider nano size (ZnO)x (ZrO2)1-x as a novel functional material. The varying calcination temperature has control over the (ZnO)x (ZrO2)1-X particle sizes by the permission of this method, so the generation of semiconductor materials with multiple band gap is possible. Detailed wavelengths of solar energy can be captured by these materials, which can be an appropriate choice for employment of solar cell applications.